1994
DOI: 10.1093/oxfordjournals.annonc.a058883
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of docetaxel (Taxotere®) in metastatic colorectal carcinoma

Abstract: Administered at the stated dose and schedule, docetaxel has little activity against metastatic colorectal carcinomas. The toxicity profile, consisting of granulocytopenia, hypersensitivity reactions, cutaneous reactions, and edema, has been previously described in patients receiving docetaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…The median survival time in case of S-1 given to colorectal cancer patients was consistent with data obtained on leucovorin·5-FU or interferon·5-FU [43, 44]. Compared to S-1, docetaxel [45]and topotecan [46]were less effective in cases of colorectal cancers. Thus, S-1 shows promise for potent antineoplastic effects on gastrointestinal cancers.…”
Section: Discussionsupporting
confidence: 82%
“…The median survival time in case of S-1 given to colorectal cancer patients was consistent with data obtained on leucovorin·5-FU or interferon·5-FU [43, 44]. Compared to S-1, docetaxel [45]and topotecan [46]were less effective in cases of colorectal cancers. Thus, S-1 shows promise for potent antineoplastic effects on gastrointestinal cancers.…”
Section: Discussionsupporting
confidence: 82%
“…There is evidence that abnormalities of the spindle checkpoint drive CIN, and in turn promote taxane resistance 154. Given that most CRCs are CIN+, this may explain the poor response of CRC to taxanes observed in phase 1 trials,155 and diploid CRCs could show a better response to taxanes.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that although single-agent capecitabine did not produce major responses in pretreated colorectal cancer patients in a recent study 15 and single-agent docetaxel has not shown significant antitumor activity in this malignancy, 16,17 the combination of capecitabine with docetaxel in this study resulted in major responses (partial response) in the two colorectal cancer patients who had been previously treated with either multiple chemotherapeutic or chemoembolization and biologic agents. It is interesting to note that although single-agent capecitabine did not produce major responses in pretreated colorectal cancer patients in a recent study 15 and single-agent docetaxel has not shown significant antitumor activity in this malignancy, 16,17 the combination of capecitabine with docetaxel in this study resulted in major responses (partial response) in the two colorectal cancer patients who had been previously treated with either multiple chemotherapeutic or chemoembolization and biologic agents.…”
Section: Discussionmentioning
confidence: 59%